Gravitational radiation from precessing accretion disks in gamma-ray bursts - Romero, Gustavo Esteban (2010)
Context. We study the precession of accretion disks in the context of gamma-ray burst inner engines. Aims. Our aim is to quantitatively estimate the characteristics of gravitational waves produced by the precession of the transient accretion disk in gamma-ray bursts. Methods. We evaluate the possible periods of disk precession caused by the Lense-Thirring effect using an accretion disk model that allows for neutrino cooling. Assuming jet ejection perpendicular to the disk plane and a typical intrinsic time-dependence for the burst, we find gamma-ray light curves that have a temporal microstructure similar to that observed in some reported events. The parameters obtained for the precession are then used to evaluate the production of gravitational waves. Results. We find that the precession of accretion disks of outer radius smaller than 108 cm and accretion rates above 1 M⊙ s-1 could be detected by Advanced LIGO if they occur at distances of less than 100 Mpc. Conclusions. We conclude that the precession of a neutrino-cooled accretion disk in long gamma-ray bursts can be probed by gravitational wave astronomy. Precession of the disks in short gamma-ray events is undetectable with the current technology.